2014
DOI: 10.1016/j.diabres.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological characteristics of diabetic patients under age 40 in Cameroon: Relation to autoantibody status and comparison with Belgian patients

Abstract: Aims We investigated the prevalence of diabetes autoantibodies (Abs) in Cameroonian patients and controls, assessed their contribution in disease classification and compared results with data from Belgium. Methods Abs against GAD (GADA), IA-2 (IA-2A) and zinc transporter 8 (ZnT8A) were assessed in 302 recently diagnosed Cameroonian patients with diabetes and 184 control subjects without diabetes aged below 40 years. Results Only 27 (9%) Cameroonian patients were younger than 15 years. Overall, 29% of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 35 publications
5
27
0
Order By: Relevance
“…1 which shows the age of presentation of a consecutive series of over 2280 diabetic patients over a 14-year period; nearly a half of the patients had T1DM. There were similar findings in a third culturally distinct area of Ethiopia, Mekelle [ 6 ], South Africa [ 7 ] and Cameroon [ 8 ]. By contrast, the pattern of disease reported from diabetes registries in the West show a much higher incidence rate in the under-15 age group (50–60%) with peak incidence at or before puberty [ 9 ].…”
Section: Type 1 Diabetes In a Resource-poor Settingsupporting
confidence: 69%
See 2 more Smart Citations
“…1 which shows the age of presentation of a consecutive series of over 2280 diabetic patients over a 14-year period; nearly a half of the patients had T1DM. There were similar findings in a third culturally distinct area of Ethiopia, Mekelle [ 6 ], South Africa [ 7 ] and Cameroon [ 8 ]. By contrast, the pattern of disease reported from diabetes registries in the West show a much higher incidence rate in the under-15 age group (50–60%) with peak incidence at or before puberty [ 9 ].…”
Section: Type 1 Diabetes In a Resource-poor Settingsupporting
confidence: 69%
“…Autoimmunity is believed to be a very important factor in the aetiology of T1DM, especially that arising in childhood. Recent studies have reported rates of islet autoantibody positivity ranging from 30% in Tanzania [ 23 ], 29–35% in Ethiopia [ 24 •, 25 ] to 43% in Cameroon [ 8 ] in T1DM. These studies have been carried out for the most part in adult patients and some in mainly urban areas.…”
Section: Islet-cell Autoimmunity In Sub-saharan Africamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of type 1 diabetes from West Africa (Cameroon) investigated an urban group shortly after clinical diagnosis and compared them with a Belgian population. As in Ethiopia, few (9%) had childhood-onset type 1 diabetes, and in those who were classified as having type 1 diabetes a very low percentage of children (≤15 years) and adults (median age 30 years) were autoantibody positive; the majority of these had GADA, and far fewer had IA-2A or ZnT8A [2]: the overall autoantibody prevalence in those classified as having type 1 diabetes was lower than in the Amhara. The adult Belgian diabetic participants had a much higher incidence of multiple autoantibodies than the Cameroonian participants.…”
Section: Autoantibody Prevalencementioning
confidence: 89%
“…There is wide genetic diversity in sub-Saharan Africa; that being the case, we have studied a single ethnic group to limit genetic diversity within this study and have emphasised that the results from the Semitic-background Amhara differ in autoantibody profile from the Bantu-background Cameroonians [2], who were investigated at a similar time, close to clinical diagnosis. Additionally, both the Amhara and Bantu have shown some differences from European background groups.…”
Section: Limitations Of the Studymentioning
confidence: 99%